Sustaining Suburbia through New Urbanism: Toward Growing, Green, and Just Suburbs? - Trudeau, Dan (2018)
This article examines the governance dynamics surrounding the development of sustainable neighborhoods in United States metropolitan contexts characterized as suburban sprawl. Drawing on original case study research of three distinct applications of New Urbanism design principles, the article argues for understanding the relative power of municipal authorities to incorporate social justice imperatives into the practice of sustainable development in suburban contexts. Moreover, key to prioritizing social imperatives is the way in which development processes respond to the “suburban ideal”, which is a view of suburbs as an exclusive bourgeois utopia that constrains the ability to connect so-called sustainable development with social justice. Case study research shows how deference to the suburban ideal limits sustainable development to embracing growth and greening interests only and peripheralizing or denying social justice. The article discusses how sustainable development endeavors can address such constraints in the effort to create alternatives to suburban sprawl that integrate the pursuit of social justice with environmental protection and economic growth.